(untitled) (Research, Society and Development, 2025)
The objective of the present study was to carry out a systematic review of the literature with the aim of gathering information about the species considered medicinal and most cultivated in the state of Minas Gerais, Brazil. The study highlights the importance of popular knowledge in the treatment of diseases, with programs such as Farmácia Viva and the National Policy on Medicinal Plants and Phytotherapeutics promoting their use and providing guidelines for the cultivation and handling of these plants. The literature search was conducted using Google Scholar, PubMed, Scielo, and Periódico CAPES. The search strategy used the Boolean operator "AND" to combine the descriptors: cultivation AND Minas Gerais AND medicinal plants. The search yielded 517 articles, of which 14 were summarized. Similar projects were identified in Minas Gerais with positive results in improving quality of life and environmental education, with the most cultivated species being Melissa officinalis, Rosmarinus officinalis, Ruta graveolens, and Cymbopogon citratus. Thus, the study reinforces the importance of promoting the dissemination of scientific knowledge about medicinal plants and strengthening assistance based on popular and scientific knowledge, aligned with public policies that encourage the use of these plants.